The Scientific Contribution of the Clinical Method in Educational Applications: A Case Study - Valeria Biasi; Paolo Bonaiuto (LED Edizioni Universitarie, 2013)
After a review of the principles of the clinical method for relevant applications in educational issues, the paper focuses on the clinical observations of a case study centred on aggressive behaviour (bullying). The advanced clinical treatment enhances the importance of processes of mental representation and symbolization as necessary requisites for allowing the socially compatible satisfaction of individual needs. A case study is reported in order to better clarify the criteria and technical devices that must be applied in order to obtain positive results. We describe the aggressive behaviour of a three-year-old child of a particular family and educational environment. The child focused overt attacks on other persons, animals and objects. Play therapy sessions brought to light a typical lack of symbolic representation in drawing and play activities. We list and explain several technical interventions which helped this child to gradually develop these abilities, improving cognitive and social attitudes, reducing and elaborating aggressiveness. A relatively short course of therapy (7 months, a total of 50 sessions) enabled this boy to enter a path of normal development. We also discuss the school's primary role in the prevention of aggressive behaviour with a specific didactic program for facilitating processes of mental representation and symbolization.